Occupational Health Services Integrated in Primary Health Care in Iran - Masoud Rafiei; Reza Ezzatian; Asghar Farshad; Maryam Sokooti; Ramin Tabibi; Claudio Colosio (Ubiquity Press, 2015)
Introduction: A healthy workforce is vital for maintaining social and economic development on a global, national and local level. Around half of the world's people are economically active and spend at least one third of their time in their place of work while only 15% of workers have access to basic occupational health services. According to WHO report, since the early 1980s, health indicators in Iran have consistently improved, to the extent that it is comparable with those in developed countries. In this paper it was tried to briefly describe about Health care system and occupational Health Services as part of Primary Health care in Iran. Methods: To describe the health care system in the country and the status of occupational health services to the workers and employers, its integration into Primary Health Care (PHC) and outlining the challenges in provision of occupational health services to the all working population. Findings: Iran has fairly good health indicators. More than 85 percent of the population in rural and deprived regions, for instance, have access to primary healthcare services. The PHC centers provide essential healthcare and public-health services for the community. Providing, maintaining and improving of the workers' health are the main goals of occupational health services in Iran that are presented by different approaches and mostly through Workers' Houses in the PHC system. Conclusions: Iran has developed an extensive network of PHC facilities with good coverage in most rural areas, but there are still few remote areas that might suffer from inadequate services. It seems that there is still no transparent policy to collaborate with the private sector, train managers or provide a sustainable mechanism for improving the quality of services. Finally, strengthening national policies for health at work, promotion of healthy work and work environment, sharing healthy work practices, developing updated training curricula to improve human resource knowledge including occupational health professionals are recommended.